A high-throughput amplicon-based method for estimating outcrossing rates - Jantzen, Friederike (Plant Methods, 2019)
BACKGROUND: The outcrossing rate is a key determinant of the population-genetic structure of species and their long-term evolutionary trajectories. However, determining the outcrossing rate using current methods based on PCR-genotyping individual offspring of focal plants for multiple polymorphic markers is laborious and time-consuming. RESULTS: We have developed an amplicon-based, high-throughput enabled method for estimating the outcrossing rate and have applied this to an example of scented versus non-scented Capsella (Shepherd’s Purse) genotypes. Our results show that the method is able to robustly capture differences in outcrossing rates. They also highlight potential biases in the estimates resulting from differential haplotype sharing of the focal plants with the pollen-donor population at individual amplicons. CONCLUSIONS: This novel method for estimating outcrossing rates will allow determining this key population-genetic parameter with high-throughput across many genotypes in a population, enabling studies into the genetic determinants of successful pollinator attraction and outcrossing. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13007-019-0433-9) contains supplementary material, which is available to authorized users.